Avaliação do potencial de mutagenicidade e toxidade da lectina hipoglicemiante de folha de Bauhinia monandra (pata-de-vaca) - Sisenando, Herbert Ary Arzabe Antezamana Costa Nóbrega (2009)
Medicinal plants have been used since antiquity to treat various human diseases. The leaves of Bauhinia monandra are widely used in Brazil as herbal remedies in the treatment of Diabetes Mellitus. From the leaves of B. monandra was purified a galactose-specific lectin, called BmoLL, which also showed a significant hypoglycemic capacity. Following the proposed rules by decree No 116 of 1996/08/08 of the Ministry of Health of Brazil, the study aimed to evaluate the potential for toxicity and mutagenicity of BmoLL from the use of tests with Escherichia coli strain CC104 (Forward mutagenesis assay) with Salmonella typhimurium strain TA (Kado test), with plasmid pBCKS (Break occurrences in plasmid DNA) and enzyme exonuclease III (Search of abasic sites). The results demonstrated that the lectin was unable to increase the frequency of reverse mutation of strains of S. typhimurium, with and without metabolic activity. However, a significant decrease in the frequency of spontaneous mutation was observed in strains of E. coli, especially in poor repair (CC104mutMmutY), indicating an antioxidant potential of the lectin. BmoLL is unable to generate genotoxic and cytotoxic damage, based on the concentrations and the tests performed